DNA Damage Changes Distribution Pattern and Levels of HP1 Protein Isoforms in the Nucleolus and Increases Phosphorylation of HP1β-Ser88 - Legartová, Soňa; Lochmanová, Gabriela; Zdráhal, Zbyněk; Kozubek, Stanislav; Šponer, Jiří; Krepl, Miroslav; Pokorná, Pavlína; Bártová, Eva (Cells, 2019)
The family of heterochromatin protein 1 (HP1) isoforms is essential for chromatin packaging, regulation of gene expression, and repair of damaged DNA. Here we document that γ-radiation reduced the number of HP1α-positive foci, but not HP1β and HP1γ foci, located in the vicinity of the fibrillarin-positive region of the nucleolus. The additional analysis confirmed that γ-radiation has the ability to significantly decrease the level of HP1α in rDNA promoter and rDNA encoding 28S rRNA. By mass spectrometry, we showed that treatment by γ-rays enhanced the HP1β serine 88 phosphorylation (S88ph), but other analyzed modifications of HP1β, including S161ph/Y163ph, S171ph, and S174ph, were not changed in cells exposed to γ-rays or treated by the HDAC inhibitor (HDACi). Interestingly, a combination of HDACi and γ-radiation increased the level of HP1α and HP1γ. The level of HP1β remained identical before and after the HDACi/γ-rays treatment, but HDACi strengthened HP1β interaction with the KRAB-associated protein 1 (KAP1) protein. Conversely, HP1γ did not interact with KAP1, although approximately 40% of HP1γ foci co-localized with accumulated KAP1. Especially HP1γ foci at the periphery of nucleoli were mostly absent of KAP1. Together, DNA damage changed the morphology, levels, and interaction properties of HP1 isoforms. Also, γ-irradiation-induced hyperphosphorylation of the HP1β protein; thus, HP1β-S88ph could be considered as an important marker of DNA damage.
Keywords: Chromosomal Proteins, Non-Histone; homolog proteinu s chromoboxem 5; poškození DNA; nucleolus; FLIM-FRET; DNA Damage; epigenetics; fosforylace; Cell Nucleolus; optické zobrazování; Fluorescence Resonance Energy Transfer; Phosphorylation; mass spectrometry; HP1; HeLa buňky; phosphorylation; lidé; irradiation; HeLa Cells; Humans; Optical Imaging; rezonanční přenos fluorescenční energie; nádorové buňky kultivované; Chromobox Protein Homolog 5; chromozomální proteiny, nehistonové; Tumor Cells, Cultured; Serine; buněčné jadérko; serin